Sustainable drying of galangal through combination of low relative humidity, temperature and air velocity - Apinan Namkanisorn; Siripan Murathathunyaluk (My University, 2020)
Galangal (Alpinia galanga) is a herb commonly grown in Southeast Asia. The galangal rhizomes contain compounds that have antimicrobial and antioxidative properties. Longer storage of galangal can be achieved by drying. In the household-based industry, farmers use tray dryers because they are relatively cheap and easy to use. However, the quality of the products is low due to inappropriate temperature and drying time. The drying process is also energy intensive. This study investigated the effects of drying conditions such as air velocity, drying temperature and relative humidity on the drying characteristics and product quality. Drying of galangal was carried out at the following conditions: air velocities 0.25 and 0.5 m/s, drying temperatures 45 and 75 ∘C and relative humidity at 15 and 70 %RH, respectively. The mathematical modeling of thin layer drying kinetics of galangal was performed using Page model. The active ingredients in dried galangal were best preserved using a drying condition at air velocity of 0.25 m/s, 45 °C and 15%RH, in which the highest values of inhibition of free radicals by DPPH, total phenolic content (TPC) and 1'-acetoxychavicol acetate (ACA) content were 79.2 ± 1.3%, 91.9 ± 3.9 mgGAE/100 g and 384.1 ± 17.6 mg/100 g, respectively. Switching the relative humidity from low to high while keeping both air velocity and temperature low yielded a low drying rate. Hence, a combination of low relative humidity and low drying temperature at the optimum air velocity is promising for the design of more energy efficient dryer that gives desirable drying characteristics and product quality.
Keywords: Tray; Air velocity; Essential Oils and Antimicrobial Activity